Prevalence of dentofacial injuries in contact sports players: a systematic review and meta-analysis - Oliveira Werlich, M.; Honnef, L. R.; Silva Bett, J. V.; Domingos, F. L.; Pauletto, P.; de Souza. B. D. M.; Duque, T. M.; Curi Hallal, A. L.; De Luca Canto, G. (Dental Traumatology, 2020)
Contact sports present intense physical contact and usually players have a high risk for dentofacial injuries. It is unclear how often these injuries occur and which collective contact sports present the highest rates. The aim of this study was to assess the prevalence of dentofacial injuries among collective contact sports participants.